Using Whispering Game to Improve Students’ Pronunciation - Karolina Mutia; Tities Hijratur Rahmah; Suhartatik Suhartatik (Journey: Journal of English Language and Pedagogy, 2024)
Most of the students said that learning English Pronunciation is difficult. A sentence will have different meaning if they wrong in pronounce it. Therefore, teaching pronunciation is one of the important parts in learning English. The design used in this study is Classroom Action Research (CAR). Technique of collecting data in this study is both quantitative data and qualitative data. The researcher uses qualitative data consist of questionnaire sheet, and interview. While quantitative data is taken from student’s score from the test, it consists of 35 students’ final pronunciation. This research was conducted at SMPN 5 Lembor. The purpose of this study is to improve students’ pronounciation skills by using whispering game. Based on finding research, whispering game can improve the student’s pronunciation ability. The result of student’s score is better than before applying the game, it means that pronunciation of students had been improved after using whispering game in English teaching learning process.